A taxonomy of podcasts and its application to higher education - Carvalho, Ana Amélia Amorim (2009)
In this paper we address the uses of podcasts in higher education. We propose a taxonomy of podcasts based on literature review and in our experience as creators and users of podcasts in our courses. We describe the results obtained within a study that is being conducted at University of Minho, in Portugal, focusing on the use of podcasts and their implications for learning in higher education. The project involves 6 lecturers from different scientific domains – Education, Humanities, Social Sciences, Engineering and Biology. These lecturers created 81 podcasts to support their undergraduate (53 podcasts) and graduate (32) courses during the 1st and 2nd semesters of 2007/ 2008 and the 1st semester of 2008/ 2009. A total of 479 students - 372 undergraduate and 107 master students - were enrolled in 20 courses. These students were not only podcasts listeners but they also had the challenge and the opportunity to create their own podcasts (34 episodes out of a total of 118 podcasts). Podcasts were classified in different types (Informative, Feedback, Guidelines and Authentic materials), styles (formal or informal), length (short, moderate or long), purpose and medium (audio or video) according to a taxonomy proposed by the authors. The majority of podcasts was Informative (76), followed by podcasts with Feedback (30), Guidelines (9) and Authentic materials (3). Most podcasts were of short length (102), mainly in informal style and only 21 vodcasts. Students´ reactions about podcasts implementation in higher education reveal their acceptance of this new tool and their receptiveness to podcasting in other courses. The majority of students found podcasts a positive resource in learning as well as the lecturers, who recognized the great potential of this pedagogical tool although identifying that it is too time consuming. However, students do not take yet the advantages of this technology as they do not use portable devices to listen to podcasts.